1987
DOI: 10.1177/154193128703100517
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Judgements of Vehicle Velocity and Distance

Abstract: The purpose of this study was to determine if older adults have more difficulty than younger adults in judging either the distance or speed of approaching vehicles. Eighteen elderly and 27 younger adults made judgements of the speed and distance of a video-taped automobile. Velocity judgements were made of 5 s segments of the car moving at 20, 30, 40, 50, and 60 mph. Distance judgements were based on 5 static sequences of the same test vehicle at 190, 235, 300, 360, and 480 ft. It was found that older women ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 4 publications
9
26
1
Order By: Relevance
“…In contrast to Hills and Johnson's data, slopes did not vary across the age groups; however, intercepts were significantly higher in older adults, indicating that the elderly judged cars to be traveling more quickly than was judged by the young. To the extent that velocity estimates from two-dimensional scenes can be generalized to roadway settings, the Scialfa et al (1987) data could be used to argue that velocity estimation per se does not differentially contribute to the accident profile of older adults, because the errors would be expected to lead to more conservative driving actions. Still, it is obvious that further work is needed.…”
Section: Aging Accident Involvement and Speed Estimationmentioning
confidence: 99%
“…In contrast to Hills and Johnson's data, slopes did not vary across the age groups; however, intercepts were significantly higher in older adults, indicating that the elderly judged cars to be traveling more quickly than was judged by the young. To the extent that velocity estimates from two-dimensional scenes can be generalized to roadway settings, the Scialfa et al (1987) data could be used to argue that velocity estimation per se does not differentially contribute to the accident profile of older adults, because the errors would be expected to lead to more conservative driving actions. Still, it is obvious that further work is needed.…”
Section: Aging Accident Involvement and Speed Estimationmentioning
confidence: 99%
“…Other researchers have concluded that the deterioration of the useful visual field with ageing leads to tunnel vision (i.e. older people always have a lower performance than younger people, and the difference in performance becomes more pronounced as the eccentricity of the signal to be detected increases) (Ball, Roenker, & Bruni, 1990;Ball et al, 1988;Scialfa, Kline, Lyman, & Kosnik, 1987;Sekuler & Ball, 1986). A similar impact of age on the ability to detect visual signals in tests carried out using a computer has been observed in experiments based on driving tasks.…”
Section: Older Driver Crashes Involving a Vulnerable Road Usermentioning
confidence: 61%
“…This result confirmed our first hypothesis that specific training in driving would lead to an increase in drivers' visual field. A review of the literature on the useful visual field highlighted the fact that the variables which lead to a deterioration of the useful visual field can result in either general interference if the deterioration is homogenous across the visual field (Seiple et al, 1996;Sekuler et al, 2000) or in tunnel vision if the deterioration becomes more marked as the degree of eccentricity of the signal to be detected increases (Ball et al, 1988(Ball et al, , 1990Rogé et al, 2003Rogé et al, , 2004Scialfa, Kline, Lyman, & Kosnik, 1987;Sekuler & Ball, 1986). Similarly, we can conclude that the training given to elderly drivers leads to an 'overall improvement' in their useful visual field.…”
Section: Discussionmentioning
confidence: 98%
“…For example, age affects the judgment of the velocity of the approaching vehicle and distance (Scialfa et al, 1987).…”
Section: Human Factormentioning
confidence: 99%